(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Ivanets N. V. A role of personality of teacher is in multicultural education of pupils of primary school. In the article the meaning of the notion «multicultural competence» is revealed, the main characteristics of the future teacher’s multicultural competence, which promote the formation of pupils’ multicultural behavior during the educational process are stated.